Shear Performance of Zirconium Alloy Welds Under Different Strain Rates - Wang, Haoyu; Zhao, Tianfei; Cao, Shuanghui; Ren, Quan-yao; Liu, Menglong; Zhang, Jibin; Zheng, Yong; Li, Yuanming; Wei, Lianfeng (Frontiers in Energy Research, 2022)
Welding is one of the important connection methods for zirconium alloy, and the shear failure under the dynamic load is a typical failure mode of the weld. Aiming at clarifying the shear failure of zirconium alloy welds, three kinds of double-notched shear weld specimens with welding sizes of 2, 4, and 6 mm were designed, respectively; the shear performance of specimens under quasi-static and dynamic loading was tested by tensile testing machine and split Hopkinson pressure bar (SHPB). The stress–strain curves and shear strength were determined for the weld under quasi-static and dynamic loading. It was demonstrated that 1) an obvious strain rate strengthening effect was observed for the shear strength performance of zirconium alloy weld; 2) the shear performance of zirconium alloy weld was not sensitive to its length, but the tolerance to micro defects in the weld was improved with the increase of the weld length, which gave rise to a small increment of shear strength; 3) the failure mode of zirconium alloy welds under quasi-static loading was the typical lamellar tearing failure, and the angle between the fracture and base metal was about 17°; however, the shear failure mode showed obvious brittle characteristics under dynamic loading and the angle between fracture and base metal was almost parallel to the loading direction.